Frequently Represented Sense Components in Memes and Demotivators Dedicated to Lockdown - M. N. Latu (Научный диалог)
The article is devoted to the study of sense components that are often represented in the content of static polycode texts, in particular, demotivators and memes devoted to the phenomenon of mass lockdown. The aim of the study is to establish the elements of knowledge, which are basic concepts and are used in the construction of messages, understanding the specifics of this mode, broadcasting opinions. The means of their expression in the verbal and non-verbal parts of polycode texts are analyzed. A different degree of their representativeness is established, depending on the frequency of the used linguistic means and non-verbal elements. The statistical data were processed using the AntConc 3.5.8 text corpus analyzer program, using the stop-list of words. Attention is paid to the differences in the actualization of the identified mental constructs in the verbal and non-verbal parts of memes and demotivators. They were systematized in accordance with this criterion. The frequency of the use of verbal and non-verbal means to convey the same semantic component is assessed in a comparative manner. The diversity of linguistic means used by the authors of memes and demotivators of the studied group is characterized.